Function generation with two loop mechanisms using decomposition and correction method. (April 2017) - Kiper, Gökhan; Dede, Mehmet İsmet Can and Maaroof, Omar W. and Özkahya, Merve
Abstract: Method of decomposition has been successfully applied to function generation with multi-loop mechanisms. For a two-loop mechanism, a function y = f(x) can be decomposed into two as w = g(x) and y = h(w) = h(g(x)) = f(x). This study makes use of the method of decomposition for two-loop mechanisms, where the errors from each loop are forced to match each other. In the first loop, which includes the input of the mechanism, the decomposed function (g) is generated and the resulting structural error is determined. Then, for the second loop, the desired output of the function (f) is considered as an input and the structural error of the decomposed function (g) is determined. By matching the obtained structural errors, the final error in the output of the mechanism is reduced. Three different correction methods are proposed. The first method has three precision points per loop, while the second method has four. In the third method, the extrema of the errors from both loops are matched. The methods are applied to a Watt II type planar six-bar linkage for demonstration. Several numerical examples are worked out and the results are compared with the results in the literature. Highlights: Three correction methods for function generation synthesis of two-loop linkages. Either of the methods may lead to superior results depending on the problem at hand. Superiority of proposed methods over other methods in the literature is illustrated.